Contemporary Modern Vision of Malaysia - Safei, Su'aidi (Ruz el-Yosouf, 2013)
Education Malaysia Egypt (EME) office in Cairo, formerly known as the Student Affairs Department, commenced its operation since 1980, at the Embassy of Malaysia in Cairo. It functions as a strategic organization and one-stop center for all aspects of higher education, serving all those in need outside Malaysia, including Malaysian students themselves and international students. Further details, activities and programs are discussed in the article.